PENGARUH SELF-CONFIDENCE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DENGAN MOTIVASI BELAJAR SEBAGAI VARIABEL MEDIASI : Survey pada Siswa Kelas XI IPS SMA Negeri di Kabupaten Cianjur - Risa Cahya Maulani, - (2020)
This research is motivated by the low student learning outcomes in economic subjects class XI IPS of SMA Negeri in Cianjur regency which is seen based on the PAS value of the 2018/2019 school year. This study aims to study the interaction of confidence in student learning outcomes in economic subjects with learning motivation as mediation. The research method used was an explanatory survey using a questionnaire / questionnaire as a data collection tool. The population in this study were students of class XI IPS of SMA Negeri in Cianjur Regency and a sample of 213 students was taken by simple random sampling technique. The data analysis technique used is multiple linear regression analysis with the Mediation Model. The results showed that self-confidence influences student learning outcomes and learning motivation mediates the effect of self-confidence on student learning outcomes.